Seasonal and diel changes in cetacean vocalizations monitored by passive acoustic methods in Nemuro Strait adjacent to the Shiretoko World Natural Heritage Site. Issue 4 (12th April 2021) - Otsuki, Mayuko; Akamatsu, Tomonari; Nobetsu, Takahiro; Mitani, Yoko
Abstract: UNESCO World Natural Heritage sites are established to ensure the long‐term conservation of natural areas. Nemuro Strait in northern Japan is adjacent to the Shiretoko World Natural Heritage Site, and attracts various trophic levels of marine species, including marine mammals. Although the coexistence of humans and marine mammals is an important issue in this area, the temporal habitat use of cetaceans in this area is unknown. Here, we document seasonal and diel changes in cetacean vocalizations collected using passive acoustic recording devices during November 2012–March 2014. Killer whale calls occurred in spring and summer, and sperm whale clicks were detected in summer. Pacific white‐sided dolphin calls were recorded in summer and late fall. No cetaceans were recorded during the sea ice period in February and March. The dolphin calls and unknown click trains were significantly more frequent at night. In contrast, marginal diel changes in killer whale calls were detected. Our results suggest that the majority of cetaceans utilize Nemuro Strait at night during the ice‐free period, and we provide new insights into the habitat use and diversity of marine mammals in the Strait.